2022
DOI: 10.5489/cuaj.7720
|View full text |Cite
|
Sign up to set email alerts
|

Under-recognized factors affecting penile implant satisfaction in patients

Abstract: Introduction: Surgical management via penile prosthesis is an option for patients who have failed medical management. There is a paucity of literature surrounding factors contributing to patient satisfaction after implant surgery. The objective of this study was to characterize patients’ and surgeons’ attitudes toward factors affecting satisfaction with this procedure. Methods: Two patient cohorts were identified and contacted via email: a medical management of erectile dysfunction (ED) cohort and a penile imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(19 reference statements)
0
0
1
Order By: Relevance
“…Of note, one review found that patient satisfaction with delayed penile implantation attempts were around 58% ( 40 ). This is distinctly lower than the 75–98% commonly reported for virgin implants ( 41 ). The decision to explant the infected device without salvage replacement of a new prosthetic is always appropriate if the patient does not want another implant.…”
Section: Preoperative Counseling and Considerations Prior To Salvagecontrasting
confidence: 58%
“…Of note, one review found that patient satisfaction with delayed penile implantation attempts were around 58% ( 40 ). This is distinctly lower than the 75–98% commonly reported for virgin implants ( 41 ). The decision to explant the infected device without salvage replacement of a new prosthetic is always appropriate if the patient does not want another implant.…”
Section: Preoperative Counseling and Considerations Prior To Salvagecontrasting
confidence: 58%